INVESTIGATION OF THE INFLUENCE OF SOME FACTORS ON THE STRENGTH AND STIFFNESS OF JOINTS WITH STAPLES AND GUSSET PLATES - Hristodorova, Desislava; Staneva, Nelly (Innovation in Woodworking Industry and Engineering design, 2023)
Joints made with staples and gusset plates are widely used in the wood frame construction of various types of furniture, due to the quick and easy production and the availability of simple technology. In this regard, their good knowledge of bending loads would help furniture designers in the design process. The investigation aims to summarize the data from the specialized literature on the values of parameters characterizing the behavior of joints with staples and gusset plates of details in wood frame, as well as to establish the influence of some key factors such as the detailed thickness, the angle between wood details of the joints, thickness and type of material of the gusset plates on their strength and stiffness under bending load.